New and noteworthy records of Mosses from Doi (Mt.) Inthanon, Chiang Mai, Chom Tong District, Northern Thailand - Narin Printarakul (2018)
Mosses new to Thailand (35 species in 29 genera) and new to Doi Inthanon (6 species in 6 genera) are reported based on collections made by the authors. Austinia tenuinervis var. micholitzii W. R. Buck and H. A. Crum, Brotherella nictans (Mitt.) Broth., Chionostomum hainanensis B. C. Tan and Y. Jia, Clastobryopsis muelleri (Dixon) Tixier, Trichosteleum stigmosum Mitt., Micralsopsis complanata (Dixon) W. R. Buck, and Fissidens schwabei Nog. are fully illustrated.